Rasio keuangan, ukuran perusahaan, dan arus kas aktivitas operasi mempengaruhi return saham: Investigasi pada perusahaan sektor properti dan Real Estate, Tbk - Setijadi, Narwastu Angelia; Indrawati, Trisa (Implementasi Manajemen & Kewirausahaan, 2023)
This study aims to test and analyze financial ratios consisting of liquidity ratios (current ratio), profitability ratios (return on assets), solvency ratios (debt to equity ratio), and activity ratios (total asset turnover), company size, and cash flow operating activities to stock returns. This type of research is quantitative research and the data used is secondary data. The selection of the sample used in this study is the purposive side. The number of samples obtained were 22 property and real estate companies with a total of 5 years of observation so that the total sample was 110 property and real estate companies. The data analysis technique used is multiple linear regression analysis with the help of the IBM SPSS program. The results of the study partially show that the current ratio, debt to equity ratio, total asset turnover, and company size have no significant effect on stock returns, while return on assets and cash flow from operating activities have a significant effect on stock returns. Simultaneously the current ratio, return on assets, debt to equity ratio, total asset turnover, company size and cash flow from operating activities have a significant effect on stock returns.